1998
DOI: 10.1161/01.atv.18.11.1691
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD9 Is Associated With Very Late–Acting Integrins in Human Vascular Smooth Muscle Cells and Modulates Collagen Matrix Reorganization

Abstract: Abstract-CD9, a member of the tetraspanin family, and very late-acting (VLA) integrins are known to associate and form functional units on the surface of several cell types. We studied the changes in expression of CD9 and ␤ 1 -integrins (CD29, VLA) in human vascular smooth muscle cells (VSMCs) under in vitro culture conditions mimicking proliferative vascular diseases. We also investigated possible interactions between CD9 and VLA integrins in VSMCs. We found that CD9 is highly expressed in VSMCs and is subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 49 publications
(45 reference statements)
1
30
0
Order By: Relevance
“…The association of various tetraspanins with integrins is documented, modulating post ligand-binding events such as adhesion strengthening or receptor recycling (Hemler, 2005;Liu et al, 2007). Although interaction of CD9 with 3 or 6 integrins has been observed in several cell types (Berditchevski, 2001), an association with 2 integrin was only reported in vascular smooth muscle cells (Scherberich et al, 1998). Our results in yeast suggest the direct interaction of these two molecules.…”
Section: Signaling Downstream Of21 Integrinmentioning
confidence: 54%
“…The association of various tetraspanins with integrins is documented, modulating post ligand-binding events such as adhesion strengthening or receptor recycling (Hemler, 2005;Liu et al, 2007). Although interaction of CD9 with 3 or 6 integrins has been observed in several cell types (Berditchevski, 2001), an association with 2 integrin was only reported in vascular smooth muscle cells (Scherberich et al, 1998). Our results in yeast suggest the direct interaction of these two molecules.…”
Section: Signaling Downstream Of21 Integrinmentioning
confidence: 54%
“…Although its exact function is unknown, previous studies implicated CD9 in cell adhesion, migration, or signal transduction (32)(33)(34). Biochemical studies have shown that CD9 is physically associated with various membrane proteins such as integrins (preferentially ␤ 1 integrin), MHC class II, CD19, CD5, or other tetraspanin members, depending on the cell types (32,(35)(36)(37)(38)(39). Collectively, these studies show that CD9 may modulate the function of associated molecules.…”
mentioning
confidence: 91%
“…They form protein complexes that are mostly composed of different tetraspanins and integrins, but can also contain members of other protein families Horvath et al, 1998;Indig et al, 1997;Lozahic et al, 2000;Mannion et al, 1996;Rubinstein et al, 1997;Scherberich et al, 1998;Serru et al, 1999;Sincock et al, 1999;Tiwari-Woodruff et al, 2001;Yauch et al, 1998). The strongest association between tetraspanins and integrins has been described for CD151 and the α3 and α6 integrins Yauch et al, 1998;Yauch et al, 2000).…”
Section: Introductionmentioning
confidence: 99%